Effects of Matrix pH on Spontaneous Transient Depolarization and Reactive Oxygen Species Production in Mitochondria - Aklima, Jannatul; Onojima, Takumi; Kimura, Sawako; Umiuchi, Kanji; Shibata, Takahiro; Kuraoka, Yusho; Oie, Yoshiki; Suganuma, Yoshiki; Ohta, Yoshihiro (Frontiers in Cell and Developmental Biology, 2021)
Reactive oxygen species (ROS) oxidize surrounding molecules and thus impair their functions. Since mitochondria are a major source of ROS, suppression of ROS overproduction in the mitochondria is important for cells. Spontaneous transient depolarization of individual mitochondria is a physiological phenomenon widely observed from plants to mammals. Mitochondrial uncoupling can reduce ROS production; therefore, it is conceivable that transient depolarization could reduce ROS production. However, transient depolarization has been observed with increased ROS production. Therefore, the exact contribution of transient depolarization to ROS production has not been elucidated. In this study, we examined how the spontaneous transient depolarization occurring in individual mitochondria affected ROS production. When the matrix pH increased after the addition of malate or exposure of the isolated mitochondria to a high-pH buffer, transient depolarization was stimulated. Similar stimulation by an increased matrix pH was also observed in the mitochondria in intact H9c2 cells. Modifying the mitochondrial membrane potential and matrix pH by adding K+ in the presence of valinomycin, a K+ ionophore, clarified that an increase in the matrix pH is a major cause of ROS generation. When we added ADP in the presence of oligomycin to suppress the transient depolarization without decreasing the matrix pH, we observed the suppression of mitochondrial respiration, increased matrix pH, and enhanced ROS production. Based on these results, we propose a model where spontaneous transient depolarization occurs during increased proton influx through proton channels opened by increased matrix pH, leading to the suppression of ROS production. This study improves our understanding of mitochondrial behavior.